Cosmological considerations on the general theory of relativity. - Einstein, Albert (Cadernos de Astronomia, 2026)
We present the translation of the article published by Albert Einstein in 1917. In it, he introduces, for the first time, a cosmological constant, a term that today plays a very important role in the standard model of cosmology. Some introductory comments are presented, followed by the Portuguese version of the text originally written in German.